Environmental Audit of Quarry: Issues of Forest Resource - Roy, Rabindra (Nepal Journal of Forestry, 2008)
The study was carried out in Annapurna Quarry Private Limited in Dhading district in the Central Development Region of Nepal. The study focuses on carrying out comprehensive environmental audit with reference to forests resources. It was observed that the quarry has positive as well as negative impact on the forest resources. It is also realized that there is a lack of professionalism in the EIA practices. Keywords: Forest, Environmental Impact Assessment, Quarry, Environmental Audit